2020
DOI: 10.1016/j.cct.2020.106013
|View full text |Cite
|
Sign up to set email alerts
|

Isradipine enhancement of virtual reality cue exposure for smoking cessation: Rationale and study protocol for a double-blind randomized controlled trial

Abstract: Cigarette smoking remains a leading cause of preventable death in the United States, contributing to over 480,000 deaths each year. Although significant strides have been made in the development of effective smoking cessation treatments, most established interventions are associated with high relapse rates. One avenue for increasing the effectiveness of smoking cessation interventions is to design focused, efficient, and rigorous experiments testing engagement of well-defined mechanistic targets. Toward this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…However, more research on the effects of VR-CET in combination with NRT is needed to confirm and nuance this hypothesis. It will be interesting to see the results from one of the protocol papers, which outlined a planned clinical trial that combined VR-CET with NRT (eg, see the study by Papini et al [ 79 ]). This study will have a larger number of participants (n=102 vs n=41 [ 20 ] and n=7 [ 21 ]), and although it does not propose a multisession VR-CET intervention or a follow-up measure, it will still be interesting to see if the results from this intervention are in line with previous findings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, more research on the effects of VR-CET in combination with NRT is needed to confirm and nuance this hypothesis. It will be interesting to see the results from one of the protocol papers, which outlined a planned clinical trial that combined VR-CET with NRT (eg, see the study by Papini et al [ 79 ]). This study will have a larger number of participants (n=102 vs n=41 [ 20 ] and n=7 [ 21 ]), and although it does not propose a multisession VR-CET intervention or a follow-up measure, it will still be interesting to see if the results from this intervention are in line with previous findings.…”
Section: Resultsmentioning
confidence: 99%
“…Given the underwhelming results that were achieved by VR-CET in terms of smoking cessation, future studies might want to explore the potential of alternative interventions. However, at present, the interest in VR-CET does not appear to have waned yet, as shown by the number of recent studies that attempt to obtain results by combining VR-CET with other therapies, such as CBT [ 42 , 89 ] and NRT [ 20 , 79 ]. It is possible that combining VR-CET with other interventions will result in a more successful intervention, as multiple aspects of nicotine addiction are addressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the (cost-)effectiveness, relevant RCTs (level VR3), including adequate follow-up periods, need to be conducted. During our literature review, we identified five study protocols that report on planned RCTs and insights into potential new treatment mechanisms [77][78][79][80][81]. The studies focus on approach-avoidance training, mindfulness-based relapse prevention, memory-retrieval extinction and the use of pharmacotherapy (Isradipine) to enhance the effect of VRET on the extinction of craving.…”
Section: Future Outlookmentioning
confidence: 99%
“…However, more research on the effects of VR-CET in combination with NRT is needed to confirm and nuance this hypothesis. It will be interesting to see the results from one of the protocol papers, which outlined a planned clinical trial that combined VR-CET with NRT (eg, see the study by Papini et al [79]). This study will have a larger number of participants (n=102 vs n=41 [20] and n=7 [21]), and although it does not propose a multisession VR-CET intervention or a follow-up measure, it will still be interesting to see if the results from this intervention are in line with previous findings.…”
Section: Vr-cet Interventionmentioning
confidence: 99%